2020
DOI: 10.1016/j.heliyon.2020.e04620
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative LC-MS/MS analysis of high-value milk proteins in Danish Holstein cows

Abstract: High-value milk proteins, which can be obtained by optimized fractionation procedures, are ideal ingredients in many food applications. Thus, a simple and robust analytical method is required for the identification and quantification of these individual milk proteins. Here, we present a liquid chromatography–tandem mass spectrometry (LC-MS/MS) method using multiple reaction monitoring (MRM) to simultaneously detect and measure target peptides of two major milk proteins, α-lactalbumin (α-LA) and β-casein (β-CN)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The calibration curves were fabricated by plotting the peak area ( y ) and mass concentration ( x , μg/mL) of each signature peptide. The established MRM-based method for quantifying fibrillin was subjected to validation (parameters as follows) according to a previous study with slight modifications . The limit of detection (LOD) and limit of quantification (LOQ) were regarded as 3.3 and 10 times the ratio of standard deviation and standard curve slope, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The calibration curves were fabricated by plotting the peak area ( y ) and mass concentration ( x , μg/mL) of each signature peptide. The established MRM-based method for quantifying fibrillin was subjected to validation (parameters as follows) according to a previous study with slight modifications . The limit of detection (LOD) and limit of quantification (LOQ) were regarded as 3.3 and 10 times the ratio of standard deviation and standard curve slope, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…These results indicated that the established method has good sensitivity and high repeatability, which was similar to the previous investigations on other protein quantifications. 14,19 Hence, a feasible MRM-based method for the quantification of sea cucumber fibrillin has been established. The method has a variety of potential applications, such as the calculation of fibrillin content in A. japonicus and monitoring of fibrillin degradation during autolysis.…”
Section: Determination Of Fibrillin Content In a Japonicus Body Wallmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, when treated with aged rat skin fibroblasts, the bovine milk β-casein–derived peptide VLPVPQK increased cell migration by decreasing IL-6 and TNF-α, nuclear transmigration of the dormant Nrf2, and cell proliferation. The peptide reverses the growth arrest in aged fibroblast cells by lessening the activities of caspase-9 and -3, retaining nuclear integrity, and downregulating NF-κB/p38MAP kinase signaling by means of decreasing phosphorylated p38MAP kinases in the cytoplasm and by Nrf2 activation [ 63 , 64 ].…”
Section: Milk Protein–derived Peptide Effects On Metabolic Syndromementioning
confidence: 99%
“…Other functional important proteins include one of the major milk proteins, β-CN, as well as the less abundant but bioactive proteins, like osteopontin and lactoferrin. For β-CN and α-LA, large biological variations in their contents in individual cow's milk were revealed, showing potentials for exploiting this to elevate the levels of these valuable components through natural means (Le et al, 2020). Production of β-CN A 2 infant formulae has also gained interest, which may lead to an increase of β-CN A 2 cows/farms.…”
Section: Possibilities For Genetic Improvement In Relation To Dairy Milkmentioning
confidence: 99%